2014
DOI: 10.1194/jlr.d048439
|View full text |Cite
|
Sign up to set email alerts
|

Separation and quantification of 2-acyl-1-lysophospholipids and 1-acyl-2-lysophospholipids in biological samples by LC-MS/MS

Abstract: This article is available online at http://www.jlr.org by specific receptors belonging to the class A G proteincoupled receptor (GPCR) family ( 1 ). To date, 16 such GPCRs have been identified, including 6 lysophosphatidic acid (LPA) receptors, 5 sphingosine 1-phosphate receptors, 4 lysophosphatidylserine (LysoPS) receptors, and 1 lysophosphatidylinositol (LPI) receptor ( 1-4 ). Recent studies of gene-targeting mice have clearly shown that these receptors function individually in various pathological and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(142 citation statements)
references
References 17 publications
2
139
0
1
Order By: Relevance
“…To overcome this limitation, we determined the LPA species using liquid chromatography-tandem mass spectrometry (LC-MS/ MS), as described previously. [22][23][24] Using this method, we were able to measure 12 acyl-chain LPA species, including 22:6 LPA, which has not been reported in any previous clinical studies, to our knowledge. Moreover, we were also able to determine other minor lysophospholipids (LPLs) (lysophosphatidylethanolamine [LPE], lysophosphatidylglycerol [LPG], lysophosphatidylinositol [LPI], and lysophosphatidylserine), the plasma concentrations of which had not been investigated in ACS subjects.…”
mentioning
confidence: 75%
“…To overcome this limitation, we determined the LPA species using liquid chromatography-tandem mass spectrometry (LC-MS/ MS), as described previously. [22][23][24] Using this method, we were able to measure 12 acyl-chain LPA species, including 22:6 LPA, which has not been reported in any previous clinical studies, to our knowledge. Moreover, we were also able to determine other minor lysophospholipids (LPLs) (lysophosphatidylethanolamine [LPE], lysophosphatidylglycerol [LPG], lysophosphatidylinositol [LPI], and lysophosphatidylserine), the plasma concentrations of which had not been investigated in ACS subjects.…”
mentioning
confidence: 75%
“…While we could not detect LPA in the eggs, small amount of LPA (0.1–0.2 nM) was found in the uterine flushing fluids from the pregnant mice (Appendix Fig S3). Interestingly, LPA with an unsaturated fatty acid (oleic or linoleic acid), a potent ligand for LPA 3 (Bandoh et al , 2000), was detected when the uteri were flushed with the saline containing albumin which is capable of extracting lysophospholipids from outer leaflet of the cells (Okudaira et al , 2014; Appendix Fig S3). LPA was hardly recovered in the albumin‐free flushing fluids (Appendix Fig S3), indicating clearly that LPA is present in the extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…(10 or 30 mg/kg), and then, bloods were collected. Collected samples were processed for LC‐MS/MS as previously performed (Okudaira et al , 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Harvat et al (13) using 2-acyl-lyso-PE generated by the Rhizopus arrhizus lipase determined a K d value for this E. coli homolog 5ϫ lower than our result determined with the LplT-Kp protein and 1-acyl isomer. It may be difficult to determine the stereoselectivity of LplT because compelling evidence from different groups has shown that 2-acyl-lysophospholipids are extremely unstable in biological solution and are quickly converted to the 1-acyl-2-lyso form by a spontaneous intramolecular acyl migration, yielding a mixture mainly containing 1-acyl-2-lysoglycerophospholipids (15,34). We cannot rule out utilization of both lysolipid isomers by Lplt/Aas on the bacterial membrane.…”
Section: Discussionmentioning
confidence: 99%